Patmut’yun azgin Netoğats - 880-01 Grigor, Aknerli, 1250?-1335? ‎ (Los Angeles)
xiv, 140 sayfa
Keywords: “The History of the Nation of Archers is a brief history of the Mongols and their arrival and conquests in the Near East over a period of 44 years (1229 to 1273). Little is known about Gregory and his sources, but he is thought to have based his History on the reports of knowledgeable informants and manuscripts that are now lost. The History is a valuable source for thirteenth century Armenian and Mongol studies. Gregory of Akner (1250 to 1335 CE) was an Armenian historian and abbot of the monastery of Akner in Cilicia.” --